Mortality and its correlation with diagnostic tests and treatment modalities in multisystem inflammatory syndrome in children admitted in tertiary care hospital of North India - Sharma, Rakesh; Sood, Ambika (Eastern Journal of Medical Sciences, 2022)
Background: The present study aimed to describe mortality and its correlation with diagnostic tests and treatment modalities among children admitted as a case multisystem inflammatory syndrome in children (MIS-C) in Indira Gandhi Medical College, Shimla. Materials and Methods: We conducted a cross-sectional study for MIS-C from January to July 2021, in the pediatric ward of a tertiary care hospital in North India. All children admitted with the diagnosis of MIS-C were included in the study. Data regarding sociodemographic factors and mortality were extracted and analyzed using Epi Info V7 software. Results: In the present study, a total of 31 children admitted as a case of MIS-C were included in the study. Of these, 23 (74.2%) were discharged after full recovery, 5 (16.1%) died during treatment, and 3 (9.7%) left the hospital against medical advice. Children presenting with severe illness, acidosis, azotemia, Hb<10gm%, Leukocytosis, abnormal RFTs, lipid profile, thrombocytopenia, deranged coagulogram, abnormal ECG, required pediatric intensive care, inotropic support, IVIG, Aspirin, LMWH, had a shorter hospital stay and a higher mortality. Statistical significance was seen with deranged renal function, thrombocytopenia, abnormal ECG, use of LMWH, and respiratory support. Conclusion: Mortality was significantly higher in children having shorter hospital stay <1 week, presenting with severe illness and deranged RFTs, thrombocytopenia, abnormal ECG, and requiring respiratory support, ventilatory support, and taking LMWH.